Factors Related to Traffic Accidents among Online Motorcycle Taxi Riders in Bekasi - Olivia, Frisilia; Seri Ani, Luh (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Online motorcycle taxi riders in Bekasi are at risk of traffic accidents, with unknown contributing factors. This study aims to determine the factors associated with these traffic accidents. Methods: This quantitative study was conducted using a cross-sectional method with a sample size of 178 riders selected through accidental sampling. Data collection was carried out from April to May 2022 by surveying riders along the road in Bekasi. The dependent variable was traffic accidents, while the independent variables included characteristics of riders, safety riding behavior, work stress, and sleep quality. Data were collected by distributing questionnaires. Analysis was carried out using the Chi-squared test and binary logistic regression. Results: This study found a correlation between the incidence of traffic accidents among online riders and sex, age, and safety riding behavior. However, factors such as education level, duration of work, period of work, knowledge of safety riding, perception of safety riding, work stress, and sleep quality were not related to traffic accidents. Conclusion: Factors such as sex, age, and safety riding behavior were found to be related to the incidence of traffic accidents among online riders. Therefore, to reduce the death rate, it is recommended that riders, especially female and young riders, prioritize safety driving behavior.